Geometrically nonlinear analysis of sandwich composite beams reinforced by agglomeration carbon nanotubes - Bui , Thi Thu Hoai; Tran, Thi Thom; Nguyen , Dinh Kien (Vietnam Journal of Mechanics, 2022)
In this work, geometrically nonlinear behavior of sandwich composite beams reinforced by carbon nanotubes is studied, taking into account the influence of agglomeration of the carbon nanotubes (CNTs). The core of the sandwich beams is homogeneous while the two face sheets are made of CNT reinforced composite with the effective material properties being estimated by the Eshelby-Mori-Tanaka approach. A first-order shear deformable nonlinear beam element is formulated in the context of the total Lagrange formulation and used to construct the discretized nonlinear equilibrium equation. The Newton-Raphson based iterative procedure is used in conjunction with the arc-length method to trace the equilibrium paths of the beams. Detail parametric studies are carried out to illustrate the influence of the CNTs agglomeration, the amount of CNT volume fraction as well as the thicknesses of face sheets on the nonlinear behavior of the structure.